A Battery-operated Portable Standard Lead ECG Monitor with Abnormal Heart Condition Detection System for Dogs - (:unkn) unknown (My University, 2017)
Long term monitoring the dog's heart condition is the best way to prevent being unable to treat the dog's heart failure in time when it occurs. Although, electro-cardio activity has been discovered by French scientist Mattencci in 1842, but there hasn't been any proper device developed so far for long term ECG (electrocardiogram) monitoring of cardiac dogs. Therefore, this paper has proposed an ECG monitor specially designed for dogs to fill this gap. The ECG monitor proposed is a 3-lead ECG monitoring system with diagnosis software that can detect heart failure, tachycardia, bradycardia, and arrhythmia according to dog's ECG signal. It mainly consists of 3 active dry electrodes that acquire dog's ECG signal; an analog front-end circuit that amplifies and filters the acquired signal; and a processor that further filters and analyzes the signal, and then it will determine if the dog is having an abnormal heart condition; finally, all results is displayed on a LCD (liquid crystal display).
Keywords: Cardiac; Dog; ECG; Monitor; Veterinary